The question of strains in AA amyloidosis - Gunilla T. Westermark; Ebba Nyström; Sofie Nyström; K. Peter R. Nilsson; Per Hammarström; Per Westermark (Scientific Reports)
Abstract The existence of transmissible amyloid fibril strains has long intrigued the scientific community. The strain theory originates from prion disorders, but here, we provide evidence of strains in systemic amyloidosis. Human AA amyloidosis manifests as two distinct clinical phenotypes called common AA and vascular AA. Glomerular amyloid deposition of the kidney defines the common form, while in the vascular type amyloid deposits are massive in the renal medulla and in arteries throughout the body, while glomeruli are spared. By electron microscopy the two types appeared morphologically different. The common type was composed of dispersed fibrils which tended to be clustered whereas the vascular type was composed of longer and more distinct less clustered fibrils. Staining with fluorescent amyloid binding ligands analyzed by hyperspectral microscopy showed differential staining patterns between the two groups supporting the notion of human AA amyloid strains. AA amyloid staining was significantly different from systemic AL amyloid. Both types of AA (common and vascular) and AL amyloid fibrils were isolated and used to seed mouse AA amyloid in groups of inflamed NMRI mice (n = 9–10 per group). All but two mice showed amyloid deposits in the spleen induced by the human seeds. Amyloid binding ligand analysis was applied on the splenic amyloid deposits and revealed no clear significant difference between mice seeded with AA fibrils from different donors being vascular or common, but the AA deposits of mice given AL fibrils showed significantly different amyloid fluorescent signals compared to all groups of mice receiving AA fibrils. The combined results support the hypothesis that AA amyloid fibril structures can vary depending on the seed and may manifest as amyloid strains.